Electronic health literacy and factors related to self-care behaviors among hypertensive patients in Nonthaburi Province - Attapornpitak, Narissara; Pekalee, Alongkorn; Therawiwat, Manirat; Sarnkhaowkhom, Chawapon (Disease Control Journal, 2025)
Electronic health literacy is a significant determinant in enabling patients to adopt appropriate self-care behaviors to prevent complications that may lead to various diseases resulting from uncontrolled hypertension. This cross-sectional study aimed to examine electronic health literacy and the factors associated with self-care behaviors among patients with hypertension in Nonthaburi Province. The sample consisted of 267 hypertensive patients. Data was collected using interview questionnaires and analyzed using descriptive and inferential statistics, including the point-biserial correlation coefficient (rpb) and Eta coefficient. The results showed that 41.05% (95% CI=35.2-46.9) of the samples had a moderate level of electronic health literacy. Factors significantly related to self-care behaviors among hypertensive patients (p<0.05) were occupation, education level, comorbidity, and electronic health literacy. Consequently, public health organizations and relevant stakeholders should implement interventions to enhance electronic health information literacy, focusing on improving patients' knowledge and comprehension regarding online health information retrieval and their capacity to make decisions from online health information for their self-care practices.